2013
DOI: 10.5812/jjm.7197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Brucella melitensis and B. abortus from Human Blood Samples Using PCR-RFLP Method

Abstract: Background:Brucella is an intracellular parasite of the disease brucellosis throughout the world. Although several molecular typing methods are introduced to find DNA polymorphism that is able to identify Brucella species and biovars, but among these methods, detection of polymorphisms by PCR-RFLP has several advantages including the easy implementation, interpretation and the ease of use for large quantities of samples. Objectives: In the current study, the technique was used for molecular typing of Brucella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…These results indicated that PCR-RFLP of omp2a gene was not able to accurately discriminate human and animal B. melitensis biovars from each other and from B. abortus. Also, comparable results were reported by Mirnejad et al and Pishva et al (6,10).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results indicated that PCR-RFLP of omp2a gene was not able to accurately discriminate human and animal B. melitensis biovars from each other and from B. abortus. Also, comparable results were reported by Mirnejad et al and Pishva et al (6,10).…”
Section: Discussionsupporting
confidence: 90%
“…and omp2b fragments and several restriction enzymes were used in various studies (10,25). In the present study, similar to other studies in Iran and different parts ofthe world, amplification of omp2a gene from clinical and animal isolates showed different sizes (50 to 500 bp) (1,26).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…PCR was performed on sequenced isolates in a 50 ul final reaction volume containing 1x PCR buffer (Thermoscientific, USA), 2 mM MgCl 2 (Thermoscientific, USA), 0.15 mM dNTPs (Thermo Fisher Scientific), 2.5 U Taq polymerase (Thermoscientific, USA), 20 pmol of primers 2aA (5'-GGCTATTCAAAATTCTGGCG-3') and 2aB (5'-ATCGATTCTCACGCTTTCGT-3') and 0.5 ug of template DNA (Cloeckaert et al, 1995;Mirnejad et al, 2013). Cycling conditions were as follows: pre-denaturation step for 5 min at 94 ºC, followed by 35 cycles of denaturation at 94 ºC for 60 s, annealing at 50 ºC for 120 s, and extension at 72 ºC for 180 s, and finally an extension step at 72 ºC for 7 min.…”
Section: Pcr-rflp Of Omp2a Genementioning
confidence: 99%
“…Conducting the omp31 PCR assay on all the isolates revealed that all carried the gene, thus confirming that they don't belong to B. abortus. In addition to that, the obtained restriction digestion pattern, P1, using HaeIII enzyme ruled out B. suis biovar 2. omp2a is another candidate and target for PCR-RFLP analysis and differentiation of species and biovars of Brucella (Cloeckaert et al, 1995;Mirnejad et al, 2013). It is considered as an immunogenic antigen in addition to being a virulence factor (Cloeckaert et al, 1996).…”
Section: Typing Of Brucellamentioning
confidence: 99%